Optimizing the Role of Tempe Makers in the Development of KAMPUNG TEMPE Potentials as the Pioneer of Food and Climate Sovereignty - Ambar Fidyasari; Sentot Joko Raharjo; Wirastika Adhihapsari (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Beji Village, Junrejo Sub-District of Batu City has been known as “Kampung Tempe” as most of the people produce tempe. Active participation from universities is definitely important to assist the production of “tempe” in Beji village. This assistance program is aimed to enhance the production of “ tempe” to optimize the production yield, time-efficiency and hygiene which also generate adequate profits. The target subjects of this social assistance program was the group of SMSE “tempe” active businessmen in “Kampung Tempe”. The program included assistance in producing “Tempe” using Glucono Delta-Lactone method. This technology was expected to be the solution to address problems related to inconsistent quality due to the use of traditional method without reducing the taste and quality. This program was administered as a training program which included advisory, demonstration and independent assistance. The results of this research showed that the program successfully improved subjects’ knowledge on the use of more efficient method which produced “tempe” with better quality within shorter time, making the cash flow more efficient